Direct Numerical Simulations of the Impact of High Turbulence Intensities and Volume Viscosity on Premixed Methane Flames - Gordon Fru; Gábor Janiga; Dominique Thévenin (Journal of Combustion, 2011)
Parametric direct numerical simulations (DNS) of turbulent premixed flames burning methane in the thin reaction zone regime have been performed relying on complex physicochemical models and taking into account volume viscosity (κ). The combined effect of increasing turbulence intensities (u′) and κ on the resulting flame structure is investigated. The turbulent flame structure is marred with numerous perforations and edge flame structures appearing within the burnt gas mixture at various locations, shapes and sizes. Stepping up u′ from 3 to 12 m/s leads to an increase in the scaled integrated heat release rate from 2 to 16. This illustrates the interest of combustion in a highly turbulent medium in order to obtain high volumetric heat release rates in compact burners. Flame thickening is observed to be predominant at high turbulent Reynolds number. Via ensemble averaging, it is shown that both laminar and turbulent flame structures are not modified by κ. These findings are in opposition to previous observations for flames burning hydrogen, where significant modifications induced by κ were found for both the local and global properties of turbulent flames. Therefore, to save computational resources, we suggest that the volume viscosity transport term be ignored for turbulent combustion DNS at low Mach numbers when burning hydrocarbon fuels.